Strategies for bioresource collection in obstetrics: the experience of the "Genofund" biobank - O. V. Pachulia; R. A. Illarionov; E. S. Vashukova; T. B. Postnikova; A. R. Maltseva; A. K. Popova; E. A. Kornyushina; O. N. Bespalova; A. S. Glotov (Кардиоваскулярная терапия и профилактика, 2025)
The article highlights the experience of the "Genofund" biobank of the Ott Research Institute of Obstetrics, Gynecology and Reproductology in bioresource collection in modern obstetrics. To create different types of collections, the following different biobanking strategies were formulated for the first time: cross-sectional and longitudinal (dynamic). Definitions are given for these approaches. The most significant advantages and disadvantages of each of them are noted. Examples of pilot studies conducted on the platform of a bioresource collection created using the complex longitudinal biobanking are given. This approach made it possible to demonstrate, using the example of microRNA analysis, the potential of studying the physiological changes during pregnancy at the present stage, as well as the prospects for finding early predictors of pregnancy complications.